One common world, two different stories: the beliefs and practices of Malaysia and South Africa traditional healers - Mohamad Diah, Nurazzura (2015)
Traditional healers are widely accepted by traditional societies but literature shows that they are extensively employed by the urban people of Malaysia and South Africa. Traditional healers, including witchcraft practitioners and spirit owners have a connection with cultural beliefs and illness irrespective of their socio-cultural background. This study attempts to identify the beliefs and practices of traditional healers in Malaysia (bomoh) and South Africa (shaman). Secondary sources are employed to obtain relevant data for this study. The data is analyzed using qualitative approach. This study reveals that traditional healers of both countries coexist with the modern healthcare system and give support to the society by fulfilling different social responsibilities such as treating illnesses, enhancing group solidarity, appeasing spirits, protecting homes, crops as well as animals. Such healers are respected in both countries. Interestingly, patients with HIV, malaria and cancer in both countries sought assistance particularly in terms of psychological and spiritual guidance, which extends the appeal of bomoh and shaman from village folks to the urbanites. Bomoh and shaman are categorized under different specialization, skills, services and accessibility which attracted different patients. However, South Africa institutionalizes traditional healers by establishing several registered organizations and laws, which are not typical in Malaysia due to its religious understanding. Thus, the position of a shaman in South Africa is more socially recognized compared to the bomoh in Malaysia. In short, the beliefs and practices of bomoh and shaman are considered as an integral part of the people and society in both countries; making them relevant until today.